PEMBATALAN PERKAWINAN KARENA HOMOSEKSUAL DITINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 (STUDI PUTUSAN PENGADILAN AGAMA JAKARTA SELATAN NOMOR 2723/PDT.G/2019/PA.JS) - Brenda Manuel Sasmita; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Marriage annulment is different from divorce. The annulment of the marriage is a ruling that states that the marriage was declared invalid so that the marriage was considered never to exist. Divorce is the dissolution of a legal and existing marriage. What are the issues contained in this thesis including the annulment of the marriage? Authors in researching the problem using normative methods are descriptive, primary, secondary, and non-legal data sourced. The results of the study describe the annulment of marriage due to homosexuality, and contain about the views of others on this case.